Impacts of Oyster Aquaculture on Subaqueous Soils and Infauna. Issue 6 (1st November 2019) - Duball, Chelsea E.; Amador, Jose A.; Salisbury, Lauren E.; Stolt, Mark H.
Abstract : Oyster aquaculture maintains water quality via filter‐feeding processes; however, few studies have investigated the impacts of resulting biodeposits on the underlying soils. In this study, we investigated the impacts of oyster aquaculture by comparing biodeposition rates, physical and chemical properties of subaqueous soils, and infaunal communities among aquaculture and control sites in three coastal lagoons in Rhode Island. Aquaculture study sites ranged in age of use from 0 (control) to 21 yr. We applied biodeposits at an equivalent amount generated by as high as 2000 oysters m −2 wk −1 to control soils and did not observe significant enrichment, suggesting that soils and infauna can process considerable amounts of biodeposit‐derived N (5.4 g m −2 d −1 ) and C (44.3 g m −2 d −1 ) quickly. Although soils under aquaculture sites received significant biodeposits (67.8–346.47 g dry wt. m −2 d −1 ), soil N and C levels were only significantly higher at the 12‐yr site and at deeper depths (5–20 cm) in 50% of sites, suggesting considerable soil processing and/or mixing. Signs of detrimental impacts on the soil environment in aquaculture sites included elevated soil pore‐water sulfide levels, independent of time in aquaculture, and a shift in infaunal community structure, favoring higher populations of deposit feeders and opportunistic species indicative of environmental disturbance. Although our results suggest that biodeposit‐derived N and C additions are offset by infaunal processing, the changes in infaunal community structure and elevated pore‐water sulfides indicate that coastal managers should consider the possibility of a decrease in soil quality as a function of aquaculture‐related site disturbance. Core Ideas: Oyster filter feeding expels N‐ and C‐rich biodeposits onto soils beneath aquaculture racks. Soils and infauna are capable of processing considerable amounts of oyster‐derived N and C inputs. Oyster aquaculture primarily affects infaunal communities and soil and pore‐water sulfide levels.